2003
DOI: 10.1007/s10310-003-0035-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimation for the timing of the internal developmental processes of acorns from fruit size in Quercus serrata Thunb. ex Murray

Abstract: To evaluate the relative importance of the factors affecting the premature abortion of acorns in Quercus serrata Thunb. ex Murray during the course of their development, inner developmental processes of acorns were observed by microscope, and applicability of the diameter of fruits (acorns with cupules) as an indicator of the inner developmental processes was discussed. Based on the observations using microscope, the developmental processes of acorns were classified into five stages; one prezygotic and four po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…The results described in the present study corresponded with previous measurements of acorn survival, fruit size growth, and internal fruit development, respectively (Kanazashi et al 1997;Kanazashi and Kanazashi 2003; see also the ''Introduction''). We also described the development and timing of abortion of acorns in the three pollination treatments.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results described in the present study corresponded with previous measurements of acorn survival, fruit size growth, and internal fruit development, respectively (Kanazashi et al 1997;Kanazashi and Kanazashi 2003; see also the ''Introduction''). We also described the development and timing of abortion of acorns in the three pollination treatments.…”
Section: Discussionsupporting
confidence: 91%
“…Based on observations of internal fruit development, Kanazashi and Kanazashi (2003) divided the development of sound acorns into five stages: stage I, from pollination to fertilization; stage II, endosperm development; stage III, from the start of cotyledon differentiation to the time when only one embryo survives to develop in the ovary; stage IV, to the period of morphological completion of the embryo; and stage V, the further development of cotyledons. Our results showed that the timing of premature acorn abortion was strongly related to acorn growth and their staging (summarized in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of their morphological development, and following the description provided by Kanazashi and Kanazashi (2003), the ZEs were assigned to one of the four stages.…”
Section: Plant Materialsmentioning
confidence: 99%
“…(Mogensen 1965;Borgardt and Nixon 2003;Kanazashi and Kanazashi 2003). However, little information exists about the relationship between morphological characteristics and internal biochemical events.…”
Section: Introductionmentioning
confidence: 97%